Public Sector Collaboration: Are We Doing It Well and Could We Do It Better? - Wilkins, Peter; Phillimore, John; Gilchrist, David (Wiley-Blackwell Publishing Asia, 2015)
Improving collaboration by public sector agencies is an important element of many public sector reforms. Common approaches include introducing responsibilities under legislation and policy decisions, the provision of information and guidance, and strengthening third-party oversight. To identify how collaboration is being practised, this paper reviews evidence from over one hundred reports by Auditors-General and Ombudsmen in Australia and New Zealand to identify key attributes of collaboration, and assesses these further by examining three reports in detail. It concludes that problems that have been known for many years continue to constrain public sector effectiveness. Although continuing existing approaches may assist in improving collaboration, the paper argues that there is a need to adopt more systematic approaches to organisational capacity for collaboration. It further identifies that changes in the external environment such as technology-based innovation may demand rapid progress and change in relation to collaboration.